2020
DOI: 10.3390/ijms21207606
|View full text |Cite
|
Sign up to set email alerts
|

Computational SNP Analysis and Molecular Simulation Revealed the Most Deleterious Missense Variants in the NBD1 Domain of Human ABCA1 Transporter

Abstract: The ATP-binding cassette transporter A1 (ABCA1) is a membrane-bound exporter protein involved in regulating serum HDL level by exporting cholesterol and phospholipids to load up in lipid-poor ApoA-I and ApoE, which allows the formation of nascent HDL. Mutations in the ABCA1 gene, when presents in both alleles, disrupt the canonical function of ABCA1, which associates with many disorders related to lipid transport. Although many studies have reported the phenotypic effects of a large number of ABCA1 variants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 120 publications
(141 reference statements)
0
21
0
1
Order By: Relevance
“…Prior studies on mutant protein–ligand complexes have produced similar results with the analysis of RMSD, H-bonds, and SASA [ 69 , 70 , 71 , 72 ]. It was also observed that the fluctuation was high for the 0–125 ns simulation compared to the 150–250 ns simulation for these three analyses, specifically for RMSD ( Figure 8 A2,B2,C2).…”
Section: Discussionmentioning
confidence: 69%
“…Prior studies on mutant protein–ligand complexes have produced similar results with the analysis of RMSD, H-bonds, and SASA [ 69 , 70 , 71 , 72 ]. It was also observed that the fluctuation was high for the 0–125 ns simulation compared to the 150–250 ns simulation for these three analyses, specifically for RMSD ( Figure 8 A2,B2,C2).…”
Section: Discussionmentioning
confidence: 69%
“…Again, to expose the changes in protein dynamics, we conducted principal component analysis (PCA), representing most of the dominant motions during the simulations [ 17 , 29 ]. Remarkably, all variants were found to have more variances than that of the wild-type, such as G11R, G32R, G120E, and A156D with variances of 60.9%, 53.9%, 53.9%, and 58.8%, respectively, in the first three PCs, whereas wild-type has a variance of 43.2%.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulation was performed by YASARA Dynamics software by using Assisted Model Building with Energy Refinement (AMBER 14) force field [ 70 , 71 ], as previously described [ 17 , 72 , 73 , 74 ]. In the beginning, structure, variants, and native were cleaned and the hydrogen bond network was optimized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico bioinformatics tools, including SIFT, polyphen, condel, CADD, DANN, FATHMM, M-CAP, MetalR, MutPred, MutationAssessor, PROVEAN, VEST3, fathmm-MKL, I mutant3.0, iSTABLE, MuPro, PhD-SNP, PANTHER, SNPs and GO, and SNAP2 have been associated for this study. SIFT [ 57 ] is a PSI-Blast logarithm-based in-silico tool that uses sequence homology and predicts the potential role of amino acid substitution on protein function [ 58 ]. The prediction value of SIFT ranges from 0 to 1.…”
Section: Methodsmentioning
confidence: 99%